2006
DOI: 10.1295/polymj.38.264
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Polymerization of Butyl Acrylate under Ultrasound Irradiation

Abstract: ABSTRACT:The microemulsion polymerization (MEP) of butyl acrylate (BA) stabilized by ionic emulsifier and initiated by oil-soluble dibenzoyl peroxide (DBP) or lauroyl peroxide (LPO) initiators have been studied under conventional (without ultrasound irradiation, CMEP) and ultrasonic (NMEP) conditions. The polymerization rate vs. conversion curve of the microemulsion polymerization of BA initiated by DBP was described by two nonstationary rate intervals. Four nonstationary rate intervals with two rate maxima ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…However, the discrepancy between the particle size distribution obtained from PSDA and cryo‐TEM analysis, visible for the large particle diameters, suggests that the PSDA software algorithm might give slight deviations from the actual particle size distribution for polydisperse samples. The here presented particle size measurements are in good agreement with published results on systems initiated by AIBN, LPO, and even with results of the microemulsion polymerization of butyl acrylate with LPO and dibenzoyl peroxide …”
Section: Resultssupporting
confidence: 92%
“…However, the discrepancy between the particle size distribution obtained from PSDA and cryo‐TEM analysis, visible for the large particle diameters, suggests that the PSDA software algorithm might give slight deviations from the actual particle size distribution for polydisperse samples. The here presented particle size measurements are in good agreement with published results on systems initiated by AIBN, LPO, and even with results of the microemulsion polymerization of butyl acrylate with LPO and dibenzoyl peroxide …”
Section: Resultssupporting
confidence: 92%
“…In our previous works, we observed that the dependence of the polymerization rate vs. conversion in the some polymerization systems is desribed by the two or even by four rate intervals with one or two rate maxima. [16,17] The aim of this study is to model the AAm polymerizations with several rate intervals. We expect that the single radicals derived from the DAR start the polymerization and the formed polyAAm associates itself and forms also aggregates with its monomer.…”
Section: Introductionmentioning
confidence: 99%
“…In the classical MiEP using an effective hydrophobe, the second maximum is more pronounced [44]. The presence of LPO and continuous accumulation of hydrophobic oligomers promote the formation of highly monomer swollen particles, additional reaction loci, and the appearance of four rate intervals [45]. The blank experiment (without DBP) shows two rate intervals and the one maximum rate.…”
Section: Resultsmentioning
confidence: 98%